Use of Ergani Copper Factory slag as an aggregate in hot mixed asphalt mixtures - Yildirim, Bekir; Kuloglu, Necati; Akyigit, Mehmet (My University, 1993)
The aim of this work is to investigate the use of Ergani Copper Factory residual slag in hot mixed asphalt layers. The copper slag was crushed in the laboratory to the required size, then subjected to abrasion, freezing and thawing, specific weight, water adsorption and stripping tests. Later, a mix design was made using Marshall Stability Method and the results were compared appropriate specifications. On the basis of the experimental results, it was concluded that the Ergani Copper Factory residual slag can be used as aggregate mixed asphalt layers.
Ergani bakir isletmeleri curufunun bitumlu sicak karisimda agrega oalark kullanilmasi
Keywords: Aggregates; Asphalt; Copper; Crushing; Freezing; Mixtures; Stripping (removal); Thawing; Water absorption; Wear of materials; Ergani copper factory; Marshall stability method; Slags